On Centralizers of 2-torsion Free Semiprime Gamma Rings - Mutlak, Abdulkareem T.; Majeed, Abulrahman H. (Iraqi Journal of Science, 2021)
In this paper, we prove that; Let M be a 2-torsion free semiprime which satisfies the condition for all and α, β . Consider that as an additive mapping such that holds for all and α , then T is a left and right centralizer.